2006
DOI: 10.1096/fj.06-7167com
|View full text |Cite
|
Sign up to set email alerts
|

Reduced rather than enhanced cholinergic airway constriction in mice with ablation of the large conductance Ca2+‐activated K+channel

Abstract: The unique voltage- and Ca2+-dependent K+ (BK) channel, prominently expressed in airway smooth muscle cells, has been suggested as an important effector in controlling airway contractility. Its deletion in mice depolarized resting membrane potential of tracheal cells, suggesting an increased open-probability of voltage-gated Ca2+ channels. While carbachol concentration-dependently increased the tonic tension of wild-type (WT) trachea, mutant trachea showed a different response with rapid tension development fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
3
36
1
Order By: Relevance
“…The optimal resting tension was determined empirically and we have found that passive tension of~5 -10 mN results in an equivalent, maximal response to high potassium stimulation. This is consistent with a number of other studies that utilize a passive tension in this range 16,17,18 . Over the first 5-10 minutes, trachea passive tension tends to decline somewhat (stress-relaxation phenomenon) and the micrometer is used to adjust the passive tension to~10 mN during equilibration.…”
Section: Representative Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The optimal resting tension was determined empirically and we have found that passive tension of~5 -10 mN results in an equivalent, maximal response to high potassium stimulation. This is consistent with a number of other studies that utilize a passive tension in this range 16,17,18 . Over the first 5-10 minutes, trachea passive tension tends to decline somewhat (stress-relaxation phenomenon) and the micrometer is used to adjust the passive tension to~10 mN during equilibration.…”
Section: Representative Resultssupporting
confidence: 91%
“…Some examples include analysis of gene knockouts of ion channels 17,20,25,26 , metabotropic receptors 27,28,29,30 , and downstream signaling cascades 31 . In addition, the antigen challenged mouse is frequently used for asthma studies 32 and the in vitro trachea preparation provides a useful assay for changes in contractility that ensues following development of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Ruth's group also observed that their BK-KO mouse model had an enhanced sensitivity to isoproterenol and that airway smooth muscle cells from BK-KO mice were depolarized with about 10 mV compared with cells from WT mice (21). However, it should be mentioned that in the absence of ␤-AR/PKA stimulation, IBTX and genetic BK channel deletion had equivalent effects on UBSM contractility (14,22,24).…”
Section: Discussionmentioning
confidence: 98%
“…However, knockout mice of the accessory calcium-sensitive ␤ 1 -subunit were not hypertensive (96). Interestingly, the BK Ca ␣-subunit deletion enhanced the expression of cGMP signaling proteins (PKG1 and IRAG) in tracheal smooth muscle and led to cholinergic bronchoconstriction in the airways (71). cGMP enhanced BK Ca activity via PKG1 in vascular smooth muscle and thereby mediated smooth muscle hyperpolarization (70).…”
Section: Other Targets For Pkgmentioning
confidence: 99%